Pitfalls in Diagnosis: JMML versus KMT2A Rearranged Juvenile AML - Liesbeth Vanheeswijck; Sanjay Tewari; Robin Dowse; Nicola Potter; Jelena Jovanovic; Caroline L. Furness; Elsje Van Rijswijk (Case Reports in Hematology)
Background. Lysine methyltransferase 2A (KMT2A) rearrangements are commonly found in juvenile acute myeloid leukaemia (AML). Although distinct diseases, there is a known clinical overlap between KMT2A-rearranged AML and juvenile myelomonocytic leukaemia (JMML). Both occur in infancy or early childhood and present with abnormal monocytosis. Case Report. We report a case of a 20-month-old girl, who presented with lethargy, recurrent infections, bruising, and marked hepatosplenomegaly. JMML was suspected after initial work-up, revealing an abnormal monocytosis without blast excess on immunophenotyping. The additional cytogenetic and molecular diagnostics, revealing a KMT2A rearrangement, was decisive for the confirmation of AML. Conclusion. This case highlights the challenges of diagnosing KMT2A-rearranged monocytic AML and the importance of careful morphological assessment in partnership with cytogenetic and molecular diagnostics to distinguish between KMT2A-rearranged AML and JMML. Moreover, the emerging role of molecular monitoring in AML is highlighted.